Analisis Model Pembelajaran Saintifik Menggunakan Literatur Terdahulu Untuk Meningkatkan Minat Baca Tenaga Pendidik - Sifa Fauziyah; Fadlaailurrahman Fadlaailurrahman; Syaira Puja Rahmadani; I Ketut Mahardika; Ernasari Ernasari (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Scientific learning has become a crucial focus in the development of modern education. However, the effective implementation of this approach often faces various challenges, especially in the context of enhancing educators' reading interest. This research aims to conduct a thorough analysis of the scientific learning model using previous literature, particularly focusing on increasing educators' reading interest. The study employs a descriptive analysis method that explores several past journals as literature review sources. The analysis findings indicate that the implementation of the scientific approach to enhance educators' reading interest still encounters several challenges, such as insufficient infrastructure support, time constraints, and a mismatch between the teaching approach and educators' needs. Nevertheless, the research also highlights significant potential for the scientific approach to enhance educators' reading interest if implemented correctly. This study is anticipated to provide a deeper understanding of the factors influencing the implementation of the scientific approach in boosting educators' reading interest.